Implementation of Muhammadiyah green school as an effort to fulfill constitutional rights - Wijayanti, Septi Nur; Setiawan, Agus Nugroho; Makrufi, Anisa Dwi (Universitas Muhammadiyah Magelang, 2021)
A healthy environment is a basic human need and a right for everyone. Muhammadiyah has a commitment to the environment, clean living and healthy education through the process of character education, but the results are not optimal. One of the solutions offered is the Muhammadiyah Green School (MGS) program. This service program is carried out to improve the insight and skills of SMP Muhammadiyah Turi in running MGS and preparing policies for implementing MGS. Community service was carried out using a community development and participatory approach, with several methods, namely community education, training, diffusion of science and technology and consultation. The MGS program at SMP Muhammadiyah Turi has been implemented through a green curriculum, green community, and green school, and green culture. Green curriculum was carried out through the integration of good values â€‹â€‹and care for the environment in subjects, local content about the environment, as well as HW scouting extracurriculars. The green community was developed by forming MGS cadres, student guardian associations to take part in the MGS program, as well as forming student picket teams. Green school is carried out by managing school resources with â€œtabulampotâ€ of rare plants, verticulture, painting school facilities, and so on. Green culture with the â€œkurasakiâ€ program, enforcement of school rules, â€œclean operationsâ€, and the installation of banners for environmental campaigns. With mentoring by teachers and guidance by the task force team, MGS at SMP Muhammadiyah Turi can create a more conducive environment for academic and social interactions, become a medium for character education, and provide fulfillment of the right to a clean and healthy environment.